The Society for Obstetric Anesthesia and Perinatology Consensus Statement on the Management of Cardiac Arrest in Pregnancy. Issue 2 (June 2015) - Lipman, S.; Cohen, S.; Einav, S.; Jeejeebhoy, F.; Mhyre, J.M.; Morrison, L.J.; Katz, V.; Tsen, L.C.; Daniels, K.; Halamek, L.P.; Suresh, M.S.; Arafeh, J.; et al.
Abstract : ( Anesth Analg . 2014;118(5):1003–1016)